REQUIREMENTS FOR CREATING MULTIMEDIA ELECTRONIC TEXTBOOKS FOR STUDENTS OF THE 9TH CLASS OF GENERAL EDUCATION SCHOOLS - Pulatov Jobir Djamalovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article recommends the use of multimedia electronic textbooks in the teaching of informatics in secondary schools. Suggestions for creating a multimedia electronic textbook on IT science are presented.